What is left of marketing for the Chief Marketing Officer? - Girão, Mel (2021)
The CMO (Chief Marketing Officer) plays a strategic role in a company and is at the heart of digital transformations and changes in the consumption patterns we face today. However, the turnover of this position is the highest among C-suite executives. This work seeks to identify the aspects that influence this high turnover through a systematic literature review. The results show that the profile, educational background, and role of CMOs in companies and their relationship mainly with the CEO are at the heart of this issue. The CMO, facing the challenges of the digital age, must reinvent themselves to include more qualitative and analytical elements in their training, incorporating new methods and tools for analyzing customer and market behavior in this digital environment. They also need to preserve and reinforce their role as the customer’s voice representative in the organization through engagement and coordination with other C-executives, many of them in new and adjacent roles, to support strategic decisions, and help the company leverage its performance. This article intends to collaborate to update academics and those in marketing concerning the changes that have occurred in the performance of CMOs and help them shape their scope in the future.